2022
DOI: 10.1155/2022/8072824
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Big Five Personality Traits and Sports Performance among Disabled Athletes

Abstract: Awareness of the psychological issues of different groups of society can help in the management of sports programs and thus improve their athletic performance. The aim of the present study was to investigate the relationship between the big five personality traits and the sports performance of disabled athletes in team sports. Three hundred and seventy-six team athletes participated in the study. Subjects completed a questionnaire of five major personality factors, and based on the information available on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…Neuroticism was the key determinant for achievement levels. It is unclear whether these personality differences were shaped during athletes' careers or existed from the beginning, suggesting that personality differences may be a consequence, rather than a cause, of athletes' success Zar et al (2022) The research highlighted a strong link between openness and athletes' performance at the national level for both genders. In contrast, the relationships between neuroticism, extraversion, and conscientiousness with athletic performance varied widely across competitive tiers.…”
Section: Referencesmentioning
confidence: 95%
“…Neuroticism was the key determinant for achievement levels. It is unclear whether these personality differences were shaped during athletes' careers or existed from the beginning, suggesting that personality differences may be a consequence, rather than a cause, of athletes' success Zar et al (2022) The research highlighted a strong link between openness and athletes' performance at the national level for both genders. In contrast, the relationships between neuroticism, extraversion, and conscientiousness with athletic performance varied widely across competitive tiers.…”
Section: Referencesmentioning
confidence: 95%
“…They found statistically significant mean score differences in the Extraversion domain, Conscientiousness domain, and Openness to Experience domain between participants doing regular sports and participants who do not involve in sports at all. Zar et al (2022) [19] conducted an interesting study on the relationship between Big Five Personality Traits and sports performance among disabled athletes. They found that disabled athletes have a significant relationship between openness and athletic performance.…”
Section: Big Five Personality Traits and Sportsmentioning
confidence: 99%
“…Essa oscilações na performance pode estar relacionado aos traços de personalidade dos indivíduos, que podem exercer uma influência significativa sobre o desempenho esportivo (14,15). Assim, o sucesso atlético pode estar relacionado com alguns aspectos da personalidade.…”
Section: Introductionunclassified
“…Embora, os atletas possam demonstrar bons desempenho nos treinamentos, os resultados nas competições podem não corresponder às expectativas. Essa oscilações na performance pode estar relacionado aos traços de personalidade dos indivíduos, que podem exercer uma influência significativa sobre o desempenho esportivo (14,15). Assim, o sucesso atlético pode estar relacionado com alguns aspectos da personalidade.…”
Section: Introductionunclassified